2018
DOI: 10.1111/jvim.15358
|View full text |Cite
|
Sign up to set email alerts
|

The use of heart rate variability analysis to detect arrhythmias in horses undergoing a standard treadmill exercise test

Abstract: BackgroundLittle is known about normal heart rate variability (HRV) in horses during exercise. It can be difficult to separate premature beats from normal beat‐to‐beat variation at higher heart rates.ObjectivesThe aim was to quantify HRV in healthy horses during a high‐speed treadmill‐standardized exercise test (HSET) and to compare with the HRV in horses observed to have arrhythmias during exercise.AnimalsThirteen healthy horses (Group H), 30 horses with arrhythmias (Group A), and 11 horses with poor performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
(40 reference statements)
2
24
1
Order By: Relevance
“…In equines, other parameters—such as serum amyloid A, which is the main acute phase protein—has proven to be useful for detection of some subclinical pathological alterations that can affect training and competition performance [ 11 ]. The promising results with HRV parameters in human studies most likely initiated several research studies using horses in response to exercise [ 12 , 13 , 14 , 15 , 16 ]. RR intervals can be measured conventionally with electrocardiogram (ECG) machines intended for use in hospitals, but this equipment is cumbersome and cannot be used in field conditions, especially on competing horses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In equines, other parameters—such as serum amyloid A, which is the main acute phase protein—has proven to be useful for detection of some subclinical pathological alterations that can affect training and competition performance [ 11 ]. The promising results with HRV parameters in human studies most likely initiated several research studies using horses in response to exercise [ 12 , 13 , 14 , 15 , 16 ]. RR intervals can be measured conventionally with electrocardiogram (ECG) machines intended for use in hospitals, but this equipment is cumbersome and cannot be used in field conditions, especially on competing horses.…”
Section: Introductionmentioning
confidence: 99%
“…RR intervals can be measured conventionally with electrocardiogram (ECG) machines intended for use in hospitals, but this equipment is cumbersome and cannot be used in field conditions, especially on competing horses. Since the availability of portable, precise HRV monitors [ 17 ], a number of investigations of HRV on horses have been performed in the time domain at rest and at exercise [ 12 , 13 , 14 , 15 , 16 ]. Only one study was found to examine cardiac parameters during competition, from saddling to unsaddling of show jumping horses [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding HRV analysis, beat-to-beat intervals were imported into the "Heart rate variability Analysis Software 1.1" (Biomedical Signal Analysis Group, University of Kuopio, Finland) and a time and frequency domain analysis was calculated. The HRV, an indicator of the activity of the autonomous nervous system, was studied as described [12][13][14]. The HRV was analyzed in the time domain and expressed as mean heart rate and mean beat-to-beat interval.…”
Section: Heart Rate Variability Analysismentioning
confidence: 99%
“…In equine medicine, the analysis of heart-rate variability (HRV) is a noninvasive tool to evaluate the sympathetic-parasympathetic interaction [5]. It has been used in animals exposed to various stimuli to evaluate the effects of medications, response to transport, pain and training [6][7][8][9][10][11], and in horses suffering from cardiac arrhythmias [8,12,13]. The HRV measurement relies on the mathematical analysis of accurately measured variations in successive inter-beat intervals, measured as RR intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results were presented by Celia Marr (Rossdales Equine Hospital and Diagnostic Centre) and JoAnn Slack (University of Pennsylvania), following on from work by Katharyn Mitchell (University of Zurich) 1 on the use of heart rate variability (HRV) tools to improve the detection of arrhythmias in exercising ECGs, with the use of objective measures or graphical representations such as Poincaré plots and HRV variables. Much was discussed about the need for a consensus on the definitions of arrhythmias—what constitutes an atrial (APC) or ventricular premature complex (VPC) and how they are diagnosed at high heart rates (HR) and during exercise, when ECG quality is frequently affected by motion artefacts and multiple leads are not available.…”
Section: Arrhythmiamentioning
confidence: 99%